Optimizing raw material inventory for production goals at About Something Coffee Palangka Raya - Andhini, Rika Dwi; Syamsudin, Achmad; Karuehni, Ina (JSM: Jurnal Sains Manajemen, 2024)
This research aims to find out whether controlling raw material supplies using the Economic Order Quantity (EOQ) method is more optimal than the conventional method applied by the About Something Coffee coffee shop. Here the researcher calculates and compares the number of raw material orders, the amount of safety stock, the reorder point, and the total cost of inventory. Data collection techniques in this research are interviews and observation. Problems faced by companies in relation to raw material inventory include optimal purchasing of raw materials, safety inventory, and total raw material inventory costs. To answer existing problems, the author uses the EOQ (Economical Order Quantity) method. Based on the research results, it shows that the economical amount of raw materials for each purchase in 2023 is 3,464 kilograms. With this figure, it is found that the ideal time to order raw materials is 7 times a year with a lead time of 52 days. The amount of safety stock needed in 2023 is 346 kilograms. From the results above, the raw material inventory according to the EOQ method and the total cost of raw material inventory according to the EOQ method are efficient. So companies can consider using the EOQ method in managing their raw material inventory.